Antidiabetic activities of entagenic acid in type 2 diabetic db/db mice and L6 myotubes via AMPK/GLUT4 pathway. (30th January 2018) - Xiong, Hui; Zhang, Shengnan; Zhao, Zhongqiu; Zhao, Ping; Chen, Lvyi; Mei, Zhinan
Abstract: Ethnopharmacological relevance: Entada phaseoloides (L.) Merr., a traditional Chinese folk medicine, has been used in treating diabetes and other inflammatory disorders. Our previous study revealed that the triterpene saponins in E.Phaseoloides possessed an antidiabetic effect in type 2 diabetic rats by activating AMP-activated protein kinase (AMPK). Entagenic acid, the principal aglycon, isolated from the seed kernels of E. phaseoloides, has been proposed to possess a significant role in the antidiabetic effect, however, its actual effect and pertinent mechanisms are still unknown. Aim of the study: The aim of the present study was to investigate the antidiabetic effect of entagenic acid in a type 2 diabetic animal model (C57BIKsj db/db mice) and its role in the regulation of glucose uptake in L6 myotubes, and to explore the possible molecular mechanisms. Materials and methods: In vivo, average weekly body weight, daily water, food intake and postprandial blood glucose levels, the intraperitoneal insulin tolerance test, glucose tolerance test, serum lipid profiles and pancreatic histopathological changes in db/db mice treated with entagenic acid orally at different doses (5, 10 and 20 mg/kg) were assessed and compared with wild-type littermates or vehicle- and metformin-treated db/db mice. In vitro, effects of entagenic acid on the glucose consumption and the phosphorylation of protein kinase B (AKT) and AMPK in L6 myotubes were evaluated. Results: In vivo, entagenic acid significantly lowered postprandial blood glucose levels but not the body weight, normalized the serum lipid imbalance, improved the impaired glucose tolerance, insulin resistance, as well as the pathological changes in pancreatic islets. In vitro, entagenic acid dose-dependently promoted glucose utilization and enhanced the translocation and expression of glucose transporter 4 (GLUT4), and phosphorylation of AMPK but not AKT. Conclusions: The present study demonstrated that entagenic acid can markedly maintain the glucose homeostasis, improve insulin resistance and ameliorate dyslipidemia. Its antihyperglycemic effect could be caused by promoting AMPK mediated cellular signaling and GLUT4 translocation in muscles. Graphical abstract: